Narrating the marginalized Oriental female - Gohar, Saddik (Acta neophilologica, 2015)
A scrutinized reading of the early fiction of Naguib Mahfouz, particularly his masterpiece Midaq Alley, reveals that the author's outward tendency to offer what seems to be a neutral presentation of Egyptian-Arab women is thwarted by a hegemonic master narrative originated in local patriarchal traditions. It either marginalizes the female subaltern downsizing her role in the fictional canvas or conflates her with a status of gender inferiority by assigning her a role which conforms to her image in the patriarchal taxonomy of Oriental women. In other words, the authorial attempt to create an objective narrative of the male/ female controversy in Midaq Alley is totally undermined by a plethora of male voices dominating the fictional text and deploying patriarchal discourses about the depravity of the female race and the invalidity of women's struggle for independence. In this context, the paper argues that due to a hegemonic narrative mechanism, Mahfouz's representation of the female protagonist conforms to domestic patriarchal visions of femininity while on the surface it masks itself as a progressive image of womanhood.
Keywords: "Midaq Alley"; colonization; diskurz podrejenega; egiptovska književnost; Egyptian literature; hegemonija; hegemony; kolonizacija; Mahfouz, Naguib, 1911-2006; patriarchy; patriarhalnost; subaltern discourse